Analisis Kepuasan Pengguna Aplikasi Driver Ojek Online Menggunakan Metode End User Computing Satisfaction (EUCS) (Studi Kasus: PT. XYZ) - Fifi Syammariah Bawardi; Aditya Rachmadi; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
For the Indonesian economy, considerable development is supported by the development of application-based or online transportation. One of the developing online transportation services is PT. XYZ. PT. XYZ has actually been established since 2011, however this company jut hit the spotlight since the investment (or installation or instalment) of the application on iOS and Android in 2015. The problems that constrained or hindered the driver often occurred to other users as well. The application requires a measurement of the level of end-user satisfaction to understand the application user satisfaction. This study aims to find out about the satisfaction of end-user of PT. XYZ online motorcycle taxi driver application using the EUCS method. This method measures satisfaction by comparing user ratings with existing systems. This method is used because it is in accordance with the problems that exist in the end user of the PT.XYZ Driver application to make benchmarks on the dimensions that exist in the End User Computing User Satisfaction (EUCS) method. Dimensions used are content (content), accuracy (accuracy), format (form), ease of use (easy to use) and timeliness (timeliness).The results of the analysis using the EUCS method of the user of the PT XYZ driver application, obtained or suggested two EUCS variables to be improved, namely the accuracy and timeliness variable.